PENERAPAN METODE TERM FREQUENCY (TF) - INVERS DOCUMENT FREQUENCY (IDF) UNTUK PENCARIAN SINONIM KATA DALAM KAMUS BAHASA DAYAK NGAJU KALIMANTAN TENGAH - Karolita, Devi; Saputra, Ade Chandra (Universitas Palangka Raya, 2018)
The available Bahasa Dayak Ngaju dictionary only in hardcopy form and only consisted of the list of words andthe meaning of them. The dictionary didn?t provide the synonym of the word we are looking for. If we want toknow the paraphrase of one particular word, we have to do it manually by searching it on all of the list of wordsin the dictionary. Therefore, this research proposed to develope a Dayak Ngaju dictionary that provide wordsynonym search. We use Term Frequency (TF) - Invers Document Frequency (IDF) algorithm that will helpsynonym searching by comparing the term emergence in the meaning of the word that we are going to look thesynonym for in all of the meaning of the words listed on the dictionary. This method will calculate the weight inall the documents based on the input query. To evaluate the methodology accuracy, we used precision and recallmethod. The results showed that after searching synonym of 100 queries, we founded that 33 queries hadsynonyms with precision = 1 and recall = 1 and all the synonyms that are found are relevant based on expert?sjustification.